Nilai Pendidikan Agama Hindu Dalam Tradisi Nyawen Sebagai Rangkaian Upacara Ngusabha Dalem Di Desa Sukawana Bangli - Ediyana, Kadek (Jayapangus Press, 2021)
Bali island, as a relatively small island, but it has quite a big name which has been able to contribute not only to Balinese life but also to life in Indonesia and even internationally. Therefore, all religious activities cannot be separated from Desa, Kala, and Patra. The Ngusabha Dalem Ceremony is held once a year, precisely at Sasih Kapitu. The Nyawen Tradition is carried out by Daha Truna or boys by working together to prepare and carry out the Nyawen Tradition. in the Ngusabha Dalem Ceremony series. The type of research carried out is qualitative research with an ex post facto approach. In collecting interview data, literature and documentation. Based on the analysis of the data results, the research results that can be obtained are as follows: (1) The Nyawen Tradition Procession is part of the implementation of the Ngusabha Dalem Ceremony in Sukawana Village. (2) The implementation of the Nyawen Tradition has several functions, namely the function of social life, religious function, cultural preservation function, (3) The value of Hindu religious education contained in the Nyawen Tradition, namely the value of Tattwa, the teachings of Karma Marga and the teachings of Sraddha. The value of ethical education in the application of the Tri Kaya Parisudha are Manacika, Wacika, and Kayika. Meanwhile, the classification of Yajña which is based on the means and method of carrying it out is Tapa Yajña, Dravya Yajña, Jnana Yajña, and Yoga Yajña.